Evaluation of Staining Reduction of Teeth Endodontically Treated with CTZ Paste through the Use of Polytetrafluoroethylene Isolation Tape - Lucas de Lima Oliveira Barbosa; Jaine Viviane Silva; Leopoldo Cosme-Silva; Daniela Maria Carvalho Pugliesi; Patrícia Batista Lopes do Nascimento; Dayse Andrade Romão; Priscylla Gonçalves Correia Leite de Marcelos; Daniel Pinto de Oliveira; Valdeci Elias dos Santos Junior (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the level of staining in teeth endodontically treated with CTZ paste with/without the use of polytetrafluoroethylene (PTFE) insulating tape and to identify the restorative material which is the most stable to pigmentation under different rhizolysis conditions. Material and Methods: 50 human deciduous incisors were selected. The teeth received CTZ filling and were divided according to whether or not PTFE was used, as well as by the length of the remaining root (1/3 or 2/3 of the root) and by the restorative material (Modified Resin Glass Ionomer Cement or Opus Bulk Resin Fill Flow). Coloration was assessed once a week for six weeks through follow-up photographs. Pearson's chi-square or Fisher's Exact tests were used for intergroup and intragroup comparisons after six follow-up examinations (p < 0.05). Results: After six weeks of evaluation, it was possible to notice that 100% of the teeth without PTFE had their crowns stained by CTZ. Only 33.33% with PTFE showed staining (p<0.01). There was no statistical difference regarding the type of filling material (p=0.695) or the residual length of the roots (p=1.00). Conclusion: Using PTFE is an effective resource in preventing coronal staining in primary teeth endodontically treated with CTZ paste, regardless of the restorative material used to close the endodontic access or even the length of the root remnant.